2012
DOI: 10.1111/j.1467-8624.2012.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Subfunctions of Attention: Differential Developmental Gateways to Literacy and Numeracy

Abstract: Attention is construed as multicomponential, but the roles of its distinct subfunctions in shaping the broader developing cognitive landscape are poorly understood. The current study assessed 3- to 6-year-olds (N=83) to: (a) trace developmental trajectories of attentional processes and their structure in early childhood and (b) measure the impact of distinct attention subfunctions on concurrent and longitudinal abilities related to literacy and numeracy. Distinct trajectories across attention measures revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
118
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 47 publications
11
118
4
1
Order By: Relevance
“…language, visuo-spatial; Steele, Karmiloff-Smith, Cornish & Scerif, 2012) and the more time we spend focused on a task, the better the learning outcome (Carroll's 'time-on-task hypothesis ', 1963). Attentional abilities follow a developmental trajectory -as children get older they get better at sustaining attention for longer periods and become less susceptible to interference from irrelevant distractors (Gaspelin, MargettJordan,& Ruthruff, 2015;Matusz et al, 2015), although attentional abilities vary between children of the same age.…”
mentioning
confidence: 99%
“…language, visuo-spatial; Steele, Karmiloff-Smith, Cornish & Scerif, 2012) and the more time we spend focused on a task, the better the learning outcome (Carroll's 'time-on-task hypothesis ', 1963). Attentional abilities follow a developmental trajectory -as children get older they get better at sustaining attention for longer periods and become less susceptible to interference from irrelevant distractors (Gaspelin, MargettJordan,& Ruthruff, 2015;Matusz et al, 2015), although attentional abilities vary between children of the same age.…”
mentioning
confidence: 99%
“…Steinmayr and colleagues (2010) showed that sustained attention is able to moderate the relationship between intelligence and school achievement in adolescents, when school achievement is measured 5 months later. Steele et al (2012) were able to show that sustained attention did not predict numeracy when measured concurrently in children aged between 3 and 6 years, but did predict numeracy performance one year later. These studies indicate that sustained attention is at the very least involved in academic achievement and learning.…”
Section: Discussionmentioning
confidence: 85%
“…While there is a distinct lack of studies on the relationship between sustained attention and fluid intelligence in children, studies looking at the relationship between academic achievement and sustained attention may be informative in this context (Steele et al, 2012;Steinmayr, Ziegler, & Träuble, 2010). These studies find that sustained attention is significantly related to academic achievement when it is measured later in time.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations